Implementing the United Nations' sustainable development goals for water and beyond in Australia: A proposed systems approach. Issue 1 (2nd January 2018) - Hall, Nina Lansbury; Ross, Helen; Richards, Russell; Barrington, Dani Jennifer; Dean, Angela J.; Head, Brian W.; Jagals, Paul; Reid, Simon; Hill, Peter S.
ABSTRACT: The 17 United Nations' Sustainable Development Goals (SDGs) form an internationally-agreed agenda for development, and include a dedicated goal for water and sanitation (SDG 6). Yet, the presentation of the SDGs potentially invites appraisal and response 'goal-by-goal'- to the possible neglect of the mutual influences between them.We applied a systems approach to understand the interrelationships in an Australian context. While there are multiple potential 'readings' of these interrelationships, our approach is intended to initiate debate around the SDG commitments. We found the SDGs for global partnerships (SDG 17) and climate action (SDG 13) are enabling influences for the other goals, and the SDG for health (SDG 3) is influenced by all the other goals. Within SDG 6, we found that integrated water resources management target (SDG 6.5) is key to achieving the other targets. Inter-sectoral collaboration by government agencies will be essential to progress achievement of the SDGs.